PERBEDAAN NEGOSIASI DALAM KONTEKS BUDAYA DAN INTERNASIONAL - Puriadi; Wilchan Robain; Cindy Hartika; Dinda Nur Aprillya; Neza Febiola; Fadli Adriva Ginting (Jurnal Riset Multidisiplin Edukasi, 2025)
Negotiation is one of the most fundamental forms of social interaction in human life. In economic, political, and social contexts, negotiation serves as the primary means to reach agreements among parties with differing interests. This process not only involves the exchange of information and bargaining but also reflects the thinking patterns, values, and social norms held by each party involved in the negotiation. This study aims to analyze the differences in negotiation within cultural and international contexts by reviewing various relevant theories and practices. This research uses a descriptive qualitative approach because its main focus is to gain an in-depth understanding of the complex social phenomenon, namely the differences in negotiation in cultural and international contexts. The difference in negotiation in cultural and international contexts can be seen from several factors. International negotiation factors include culture and communication style, perception of time, power structures and hierarchy, social and religious values, business ethics and norms. Meanwhile, cross-cultural negotiation factors involve conducting cultural research before negotiation, adjusting communication style, prioritizing relationships and trust, developing active listening and empathy skills, and creating a win-win solution.